The genealogy of morals - Nietzsche, Friedrich Wilhelm (Modern library of the world's best books, 1887)
First essay: "Good and evil", "Good and bad".--Second essay: "Guilt", "Bad conscience", and the like.--Third essay: What is the meaning of ascetic ideals?--Peoples and countries, tr. by J.M. Kennedy.